Beyond Stress Granules: G3BP1 and G3BP2 Redundantly Suppress SARS-CoV-2 Infection - Duo Xu; Mahamaya Biswal; Quanqing Zhang; Christine Light; Yijie Wu; Chenjin Ye; Luis Martínez-Sobrido; Jikui Song; Rong Hai (Viruses)
The global pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has posed unprecedented challenges to public health and economic stability. Central to SARS-CoV-2 pathogenesis is its ability to evade the host immune response by hijacking host pathways via the interaction between viral and host proteins. We identified Ras-GTPase-activating protein SH3 domain-binding protein 1/2 (G3BP1/G3BP2) as a critical host factor that interacts with the viral nucleocapsid (N) protein, emerging from a comparative analysis of proteomic data from multiple studies. We revisited the underlying molecular mechanisms by confirming the residues required for the interaction between G3BP1/G3BP2 and SARS-CoV-2 N protein and showed that this interaction disrupts stress granule formation. Intriguingly, we observed that the ablation of both G3BP1 and G3BP2 enhanced SARS-CoV-2 replication. Our data collectively supports the notion that G3BP1 and G3BP2 play a critical role in modulating the host–virus interface during SARS-CoV-2 infection, and that their multifaceted function in cellular defense extends beyond the stress granule pathway.